Зависимость численности и вредоносности песчаного медляка (Opatrum sabulosum L.) от гидротермических условий - Миноранский, В.А. (Вестник зоологии, 1973)
Hydrothermal conditions affect greatly the character of nutrition and harmfulness of Opatrum sabulosum L. At high temperature and low humidity of the environment the beetles feed on green plants very intensively, at low temperature and high humidity of the air and soil the dead plant remains become dominating in their food. This fact may explain the different harmfulness of 0. sabulosus L. in the northern and southern regions of the distribution area and in the years with early, warm and cold rainy spring. In areas requiring irrigation the 0. sabulosum L. quantity is smaller, intensity of their nutrition with green plants decreases, the portion of plant remains in food ration increases, the resistance of plants to damages made by 0. sabulosum grows.